The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/hon.2035
|View full text |Cite
|
Sign up to set email alerts
|

Tumour burden at diagnosis as the main clinical predictor of cell resistance in patients with early stage, favourable Hodgkin lymphoma treated with VBM chemotherapy plus radiotherapy

Abstract: We verified whether early resistance to treatment can be predicted in a subset of patients with very favourable, early stage Hodgkin lymphoma, treated with VBM (vinblastine, bleomycin and methotrexate) chemotherapy and involved-field radiotherapy, an effective combination with very low early and late toxicity. The relative tumour burden (rTB) was volumetrically measured from the staging computed tomography and analysed together with the parameters of pre-therapy evaluation in 61 patients enrolled into the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
1
1
1
Order By: Relevance
“…In our study, 56.7% of the participants had relapsed. Therefore, our findings were different compared to earlier studies [25,[26][27][28].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, 56.7% of the participants had relapsed. Therefore, our findings were different compared to earlier studies [25,[26][27][28].…”
Section: Discussioncontrasting
confidence: 99%
“…The study by Sindhu [ 23 ] supported our data and showed that bulk volume was not recognized as a risk factor for HL. Many hospitals utilize low-dose radiation on patients who have refractory or partial responses to chemotherapy to lower the risk of subsequent cancers [ 26 ]. Patients in our research received radiation at a rate of 11.6%, thus results from our investigation are very much similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Предприняты разработки по созданию статистических моделей, в которые помимо объема опухолевого поражения включен и вариант лечебной программы. При анализе четырех групп пациентов, получивших схему полихимиотерапии BEACOPP с ЛТ при распространенных стадиях (n =107) [30], ABVD с ЛТ в тех же режимах (n =117), ABVD с ЛТ при всех стадиях (n =129) [31] и VBM (винбластин, блеомицин, метотрексат) с ЛТ в группе с благоприятным течением (n=61) [32], выяснили, что наиболее значимым фактором прогноза для риска развития первичной резистентности был именно объем опухоли. Несмотря на различия в лечебных программах, во всех группах отмечена существенная прямая корреляция между объемом поражения и вероятностью резистентности заболевания.…”
Section: объем опухолевого поражения как предиктивный фактор прогнозаunclassified